The USA and Tuvan People’s Republic: issues of book exchange (on documents of the State Archives of the Republic of Tuva) - M. S. Maadyr (Библиосфера)
The article examines the attempts of the Library of Congress of USA to establish contacts for book exchange with the Tuvan People's Republic. This fact took place in the second half of the 30s in the XX century. However, the Tuvan side, as evidenced by the analysis of well-known archival documents, did not provide any answers. Such attitude of the Tuvan People's Republic authority is explained by a number of reasons. One of them was a geopolitical situation both at the global and regional levels. Complicated circumstances were observed in the Tuvan People's Republic by that time, under which conditions it was not appropriate to react to «imperialist states» appeals, in particular, on book exchange at the international level.